Estudo de viabilidade econômica da implantação do sistema de aproveitamento de águas pluviais no restaurante universitário da Ufersa Caraúbas - Leal, Pedro Rafael de Freitas Fernandes (Universidade Federal Rural do Semi-Árido, 2019)
The utilization of rainwater through capture and storage systems are simple alternatives that aim to minimize the consumption of treated water, provided by the concessionaires, besides being a simple and sustainable way of obtaining water. In Brazil, especially in regions suffering from long periods of drought, such as the city of Caraúbas, it is increasingly necessary to use new methods, such as the use of rainwater, in order to meet growing demands due to population increase and pollution of water sources. The objective of this work is to analyze the economical viability of installing the rainwater harvesting system to be used to maintain the cleanliness of the UFERSA Restaurant, located at the Caraúbas campus of the Universidade Federal do Meio-Arrido. Based on the elaborated project, the efficiency of two distinct volume reservoirs was analyzed, the first of 10m³ with capacity to supply the demand for 7 months and the reservoir of 60m³ that can supply the demand throughout the year. From the costs arising from the implementation of these systems, payback was calculated, the time period for the return of the investment. The analysis of the two systems showed that their implantations are economically unviable since the return time for the 10m³ and 60m³ reservoirs are 54.6 years and 31.69 years respectively.
Monografia
Keywords: Reservatório; Tempo de retorno; Viabilidade; Captação de águas pluviais; Sustentabilidade; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA